Tahap Pemikiran Komputasional dan Hubungannya dengan Prestasi Akademik Pelajar PISMP di Sarawak - Soon, Lu Cheng; Mustafa, Jamilah (Selangor Humaniora Review, 2018)
Computational Thinking is a process that involves formulating a problem and expressing its solutions(s) in such a way that a computer-human or machine-can effectively carry out. The recent focus on computational thinking as a 21st century key skill for all students has led to a number of curriculum initiatives to embed it in K-12 classrooms. In Malaysia, the components of Computational Thinking have been integrated into the content of the New Primary School Standard Curriculum (KSSR) to be taught across all subjects in primary schools in stages starting from primary one to primary six. The aim of this study is to identify the level of Computational Thinking among PISMP final semester students and its relationship to their academic achievement, before they are posted to primary schools throughout the country. The design of the study is a quantitative type of survey. An online instrument has been used to collect the data. It comprises of 36 objective questions which were adapted from three sets of past year international competitiveness competition test on the www.bebras.uk site, organised by the University of Oxford. It consists of six constructs (Decomposition, Pattern Recognition, Abstraction, Algorithm, Logical Reasoning and Assessment) and each construct contains three different levels of difficulty questions. A total of 100 female students and 22 male students from four institutes of Teacher Education in Sarawak participated in this study. The data obtained were analyzed descriptively and inferred by using SPSS15 software. The findings shown that the level of PISMP students’ Computational Thinking skills as a whole is at moderate level only (mean = 20.08). While, the results of the Pearson Correlation Statistic have shown that the relationship between the overall level of Computational Thinking and the academic achievement is at a weak level (correlation coefficient = 0.099) at a significant level of 0.05. The findings suggest that the Malaysian Teachers Education Institute (IPGM) should design a special Computational Thinking course to be taught in IPG in future so that the IPG students will be more confident and competent in teaching computational thinking components across the new KSSR curriculum.